2017
DOI: 10.1101/135681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpreting Temporal Fluctuations in Resting-State Functional Connectivity MRI

Abstract: Resting-state functional connectivity is a powerful tool for studying human functional brain networks. Temporal fluctuations in functional connectivity, i.e., dynamic functional connectivity (dFC), are thought to reflect dynamic changes in brain organization and non-stationary switching of discrete brain states. However, recent studies have suggested that dFC might be attributed to sampling variability of static FC. Despite this controversy, a detailed exposition of stationarity and statistical testing of dFC … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 121 publications
0
78
0
Order By: Relevance
“…(g) Dynamic network construction approach. Recent studies have suggested that sliding window correlation analysis with a short window width could introduce artificial fluctuations in estimating DFC (Hindriks et al, 2016;Liegeois, Laumann, Snyder, Zhou, & Yeo, 2017;Lindquist et al, 2014). Thus, in this study, a long window width of 100s was adopted to avoid this issue.…”
Section: Validation Analysismentioning
confidence: 99%
“…(g) Dynamic network construction approach. Recent studies have suggested that sliding window correlation analysis with a short window width could introduce artificial fluctuations in estimating DFC (Hindriks et al, 2016;Liegeois, Laumann, Snyder, Zhou, & Yeo, 2017;Lindquist et al, 2014). Thus, in this study, a long window width of 100s was adopted to avoid this issue.…”
Section: Validation Analysismentioning
confidence: 99%
“…Dynamic functional connectivity (dFC) allows for timeresolved analyses of network synchronization by computing functional connectivity over brief segments of time [Hutchison et al, 2013;Zalesky et al, 2014]. Studies employing dFC have shown that synchrony of large-scale brain networks is temporally unstable [Chang and Glover, 2010], although, whether this instability is due to true neural dynamics or some type of physiological or measurement noise, or randomness in signals, is currently debated [Handwerker et al, 2012;Hindriks et al, 2016;Laumann et al, 2016;Nikolau et al, 2016;Liegeois et al, 2017]. Nonetheless, numerous studies have identified a seemingly functional role for dFC in ongoing brain dynamics, either at rest [for a review, see Preti et al, 2017] or during task engagement .…”
Section: Temporal Dynamics Of Emotions and Stressmentioning
confidence: 99%
“…Thus, any null model of multivariate timeseries whose characteristics are highly consistent with empirically observed fMRI-based brain measurements has little utility, since the phenomenon that it is testing for is ubiquitous rather than rare. The space of SCC multivariate Gaussians replicates real fMRI network timeseries with sufficient fidelity to induce broad consistency in measurable characteristics between the simulated data and the empirical data it was modeled upon 12 . Moreover, there is no a priori reason to believe that aberrant or "tail" phenomena in this space should be more strongly associated with functionally-relevant brain dynamics than with measurement noise, motion or other artifacts, e.g., the sort of features that might warrant examining a scan for possible removal rather than positioning it as an exemplar of functionally-relevant resting state brain dynamics.…”
Section: Statistical Stationarity Gaussianity and Rs-brain Dynamicsmentioning
confidence: 99%
“…This example illustrates the difficulties of building hypothesistesting frameworks for phenomena whose distinguishing quantifiable characteristics are not well understood. If, in contrast to 9 , one realizes that the space within which one is working contains the very dynamics that one is trying to rule out (a point subsequently made by 12 ) the conclusions that can be made are unconvincing and uninteresting.…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%